Comparison between efficacy of spinal mobilization with leg movement versus McKenzie technique in patients with lumbar disc herniation - Selim, Mohammad N.; Mokhtar, Maha M.; Mohamed, Mahmoud H.; Abonour, Asmaa A.; Abdelmutilibe, Sahar M.; M. Essa, Mohamed M. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
Background: Lumbar disc herniation (LDH) is one of the most common causes of medical consultation in the orthopedic clinics. LDH is believed to be the root cause of 60-80 percent of low back pain cases over a lifetime. Objective: The current study aims to evaluate the effectiveness of different dissimilar manual therapy techniques (Mulligan’s spinal mobilization with leg movement versus McKenzie technique) in patients with lumbar disc herniation. Design: The present study is a randomized control trial in which 45 individuals diagnosed with LDH were recruited as the participants of the study (mean age 48.54 ± 5.8 years). The participants were randomly allocated into three groups, with n=15 in each group. Intervention: Participants of the group A (Experimental group A) received Mulligan spinal mobilization with leg movement and T.E.N.S. (Transcutaneous Electrical Nerve Stimulation). Group B (Experimental group B) participants received McKenzie technique. Group C (control group) participants only received T.E.N.S. for four weeks. All patients in the three groups received 3 sessions each week. Pain, functional disability, and the H reflex were the primary outcome measures. The visual analogue scale (VAS) was used to assess pain, the Oswestry disability scale was used to assess functional disability, and electromyography was used to assess the H reflex. Results: Significant improvements were seen in the participants of group A, with reduction in the intensity and severity of pain, decreased level of functional disability and improvement in the H reflex, in comparison with other groups. Conclusion: Spinal mobilization with leg movement was more effective than McKenzie technique and TENS to reduce pain and functional disability, and to improve the H reflex, in individuals suffering from lumbar disc herniation.